Mesothelial proteins are expressed in the human cornea - Jirsova, Katerina; Neuwirth, Ales; Kalasova, Sarka; Vesela, Viera; Merjava, Stanislava (Experimental eye research, 2010)
The goal of our study was to determine whether proteins typical of the human mesothelial cell phenotype, such as mesothelin, HBME-1 (Hector Battifora mesothelial cell-1) protein and calbindin 2, are expressed in the human cornea, especially in endothelial cells. Cryosections and endothelial and epithelial imprints of sixteen human cadaverous corneoscleral discs were used. The presence of proteins was examined using immunohistochemistry and Western blotting, while mRNA levels were determined by qRT-PCR. A strong signal for mesothelin was present in the corneal epithelium, while less intense staining was visible in the endothelium. Similarly, higher and lower mRNA levels were detected using qRT-PCR in the corneal epithelium and endothelium, respectively. HBME-1 antibody strongly stained the corneal endothelium and stromal keratocytes. Marked positivity was present in the corneal stromal extracellular matrix, while no staining was present in the sclera. Calbindin 2 was detected using immunohistochemistry and Western blotting in the corneal epithelium, endothelium and stroma. qRT-PCR confirmed its expression in epithelial and endothelial cells. Three proteins expressed constitutively in mesothelial cells were detected in the human cornea. The possible function of mesothelin in cell-cell contact on the ocular surface is discussed. The presence of HBME-1 protein in the endothelial layer may indicate a still unknown function that could be shared with mesothelial cells of the pleura and peritoneum. The much more pronounced occurrence of calbindin 2 in the corneal epithelium compared to fewer positive endothelial cells explains the higher turnover of epithelial cells compared to the proliferatively inactive endothelium.
Keywords: GPI-Linked Proteins; fluorescenční protilátková technika nepřímá; RNA, Messenger; GPI-vázané proteiny; Male; mezotelin; Calbindin 2; western blotting; Epithelium, Corneal; stroma rohovky; membránové glykoproteiny; oční proteiny; Corneal Stroma; mužské pohlaví; Fluorescent Antibody Technique, Indirect; Endothelium, Corneal; lidé středního věku; polymerázová řetězová reakce s reverzní transkripcí; Blotting, Western; rohovkový endotel; lidé; ženské pohlaví; Biomarkers, Tumor; Humans; S100 kalcium vázající protein G; Eye Proteins; Membrane Glycoproteins; Reverse Transcriptase Polymerase Chain Reaction; Immunoenzyme Techniques; S100 Calcium Binding Protein G; kalbindin 2; Female; Mesothelin; imunoenzymatické techniky; messenger RNA; nádorové biomarkery; Middle Aged; rohovkový epitel